Constructing fair-exchange protocols for cloud computing - Cai-hui LAN; Cai-fen WANG (Tongxin xuebao)
The existing fair-exchange protocols can't be run in cloud servers, because the user's data aren't stored in local computers, but be escrowed to ‘clound'. An anonymous conditional proxy re-encryption scheme was constructed and its security was proved in random oracle model based on modified decisional bilinear Diffie-Hellman problem. At the same time, a fair-exchange protocol based on their scheme was designed, it can be employed when two users exchange their data information in cloud.